2005
DOI: 10.1002/crat.200410443
|View full text |Cite
|
Sign up to set email alerts
|

The influence of supersaturation on crystal morphology – experimental and theoretical study

Abstract: The surface docking approach of molecular modeling for prediction of crystal morphology in the presence of additives is further developed in this work. It is modified in order to take into account the influence of supersaturation on the crystal habit. With the introduction of the BCF theory and the 2-D growth mechanism in the above mentioned approach predictions have been carried out for paracetamol and caprolactam crystals, respectively. The verifications by crystals grown from solutions as simulated by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The preferable growth occurs with impurity concentration associated with supersaturation and surface energy. During the β‐Ga 2 O 3 nanowire growth, the Cu atoms were dissolved in the gallium solution with various contents, the supersaturation degree would decrease, and then the β‐Ga 2 O 3 nanowire growth was facilitated 26, 33, 34. And the morphologies of β‐Ga 2 O 3 nanowires may be influenced by affecting the supersaturation condition and surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…The preferable growth occurs with impurity concentration associated with supersaturation and surface energy. During the β‐Ga 2 O 3 nanowire growth, the Cu atoms were dissolved in the gallium solution with various contents, the supersaturation degree would decrease, and then the β‐Ga 2 O 3 nanowire growth was facilitated 26, 33, 34. And the morphologies of β‐Ga 2 O 3 nanowires may be influenced by affecting the supersaturation condition and surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…The -Fe 2 O 3 nanostructures would be formed on the iron surface when the droplets got supersaturated, and the growth would be terminated when the liquid is condensed into the solid state during cooling down (Kim et al, 2006;Yu et al, 2006). The -Fe 2 O 3 nanostructure growth should be controlled by the Fe surface diffusion and supersaturation (Lu & Ulrich, 2005;Takagi, 1957;Ye et al, 2005;. In this study, the transformation from nanowire growth to nanobelt growth or even microcrystal growth was observed in Figs.…”
Section: α-Fe 2 Omentioning
confidence: 62%
“…9 and 13. It is generally suggested that high supersaturation favors the two-dimensional growth of the nanostructures (Lu & Ulrich, 2005;Ye et al, 2005;. At low temperatures (below 600 ºC), few droplets were formed and the diffusion rate was very low, thus sparse nanowires were grown (Fig.…”
Section: α-Fe 2 Omentioning
confidence: 99%
“…An approach similar to surface docking developed to predict the influence of additives on the crystal morphology has been employed here [20][21][22][23][24][25][26]. The basis of this approach is to analyze the effect of additives on the individual crystal faces, which are cleaved from a crystal.…”
Section: Introductionmentioning
confidence: 99%